Characterization of CoWO4 nano-particles produced using the spray pyrolysis - Thongtem S. (2014)
CoWO4 nano-particles were produced by spraying the solution containing CoCl2·6H2O and Na2WO4·2H2O on glass slides at 250-450 °C. XRD, SAED, TEM, HRTEM and AFM revealed the presence of CoWO4 nano-particles with their crystallographic planes aligning in systematic array. Raman spectra provide evidence of the wolframite structure, corresponding to the product phase. Their photoluminescence (PL) emissions show the narrow central peaks of the same spectral region at 411-419 nm. © 2008 Elsevier Ltd and Techna Group S.r.l.